Studying Elections in India: Scientific and Political Debates - Stéphanie Tawa Lama-Rewal (South Asia Multidisciplinary Academic Journal)
Election studies (which are here defined as scholarly work focusing on the major phases of the electoral process, i.e. the campaign, the vote, the announcement of results and subsequent government formation) constitute a distinct sub-genre of studies on democracy, which focuses, so to speak, on the ‘mechanics’ more than on the ‘substance’ of representative democracy. This sub-genre, being relatively more visible than other studies of representative democracy, has specific implications, in the academic but also in the political arena, which are the focus of this critical review of the literature on Indian elections since the 1980s. The paper argues that election studies are really in between science and politics, and that it is important, therefore, to contextualize them.